Diffusion Tensor Imaging Connectomics Reveals Preoperative Neural Connectivity Changes in Children with Postsurgical Posterior Fossa Syndrome. Issue 2 (6th January 2020) - Meoded, Avner; Jacobson, Lisa; Liu, Ann; Bauza, Colleen; Huisman, Thierry A. G. M.; Goldenberg, Neil; Weiner, Howard; Jallo, George; Jackson, Eric
ABSTRACT: BACKGROUND AND PURPOSE: Posterior fossa syndrome (PFS), characterized by loss of language and other neurological impairments within the immediate postoperative period, occurs in approximately 25% of children who undergo surgical resection of posterior fossa tumors. Diffusion tensor imaging connectomics offer promise for elucidation of pathway‐level disruption in neural connectivity of patients with this disorder. We aim to determine differences in pre‐ and postoperative connectomics between children with PFS and children with mild or no language deficit after surgery. METHODS: Pre‐ and postoperative diffusion tensor imaging connectomics were applied and compared among patients with PFS, mild deficits, and intact language. RESULTS: A total of 35 patients were included in the study. Twenty‐three patients with preoperative data and 24 patients with postoperative data were included in the analysis. Mean ages: PFS—8.5 years, mild–3.1 years, intact language—9.4 years ( P = .02). Diagnoses included medulloblastoma (44.1%), pilocytic astrocytoma (28.6%), ependymoma (8.6%), other (11.4%), and unknown (8.6%). Five (21.7%) patients had PFS, 4 (17.4%) had mild deficits, and 14 (60.9%) had intact language. The assortativity coefficient was significantly higher in patients with PFS when compared to patients with mild deficits ( P = .023). In the connectometry analyses, decreased connectivity was found involving the corpus callosum, right corticothalamic pathway, and right corticostriatal pathway in patients with PFS when compared to patients with intact language. CONCLUSIONS: Our findings revealed significant differences in preoperative neural connectivity involving the corticothalamic and other pathways among children who did, versus who did not, develop PFS postoperatively. Diffusion tensor imaging connectomics offers a unique opportunity to study the effect of the posterior fossa tumors on cerebello‐cerebral networks and provide new insights into the mechanism of the structural plasticity/reorganization after surgery.